Effects of Muscle-Strengthening Intervention Exercise on Pain Alleviation and Postural Control in Patients with Chronic Low Back Pain - Sungyung CHUN; Kyoungkyu JEON (Tehran University of Medical Sciences, 2019)
No Abstract###